87Sr/86Sr ISOTOPE RATIOS IN THE RIVER WATERS OF THE SOUTHERN URALS - D. V. Kiseleva; E. S. Shagalov; T. G. Okuneva; N. G. Soloshenko; А. D. Ryanskaya; E. A. Pankrushina; S. V. Karpova; K. K. Urazov; A. R. Sidoruk (Геодинамика и тектонофизика)
87Sr/86Sr isotopic ratios are widely used to identify strontium sources and study strontium behaviour in(bio)geochemical cycles. 87Sr/86Sr in surface waters can reflect the average composition of bioavailable (i.e. available forfurther absorption by plants and animals) strontium in the catchment specific area. Based on those 87Sr/86Sr ratios, theregional maps of the bioavailable strontium distribution (strontium isoscapes) can be compiled. A complex block structurecharacterizes the Ural mountain system. Individual parts (blocks) are composed of rocks of various ages, genesis andgeochemical characteristics, which can radically change at a distance of several tens of kilometres. Such variability wouldbe reflected in strontium isotopic ratios, thus making it possible to determine the local isotopic signatures of bioavailablestrontium.This work aimed to study 87Sr/86Sr in the water in the rivers of the Southern Urals. We determined the contents andisotopic ratios of strontium in river water samples collected from the territories of the Orenburg and Chelyabinsk regionsand the Republic of Bashkortostan in 2019–2020.For the first time in the surface water of the rivers in the Southern Urals (Ural, Belaya, Tobol, Karagaily-Ayat, Sim, andothers), the 87Sr/86Sr isotopic ratios have been determined, and their variations have been analyzed. 87Sr/86Sr values varyin the range 0.70666–0.71063 (average 0.70908) for the rivers of the Urals basin, 0.70749–0.71058 (average 0.70924)for the Kama-Volga basin, 0.70946–0.71176 (average 0.71071) for the Tobol basin. Such features of the strontium isotopiccomposition may be due to the influence of underlying rocks of the catchment area drained by river water. The dataobtained can be used to identify the sources of strontium input into the water system during hydrological and environmentalstudies; to confirm the authenticity of food products of plant and animal origin; to carry out comparisons in thestudies of the migration of ancient people and animals, as well as to determine the raw material areas for the productionof vegetable and woollen textiles and wooden products in antiquity.